THE IMPACT OF ENTREPRENEURIAL GROWTH MINDSET ON ENTREPRENEURIAL PERFORMANCE MEDIATED BY TECHNOPRENEURIAL COMPETENCIES IN SMEs - Nobelson Nobelson; Suharyati Suharyati (Jurnal Ekonomi, 2023)
This research aims to examine the impact of an entrepreneurial growth mindset on entrepreneurial performance by involving technopreneur competencies as a mediator. Quantitative research was conducted with 100 micro sector MSMEs in the Sawangan and Bojongsari areas, Depok City as samples, using the purposive sampling method. Data analysis was carried out using Smart PLS 3.0 software. The results of the SEM PLS analysis show that the entrepreneurial growth mindset has a positive and significant effect on technopreneur competence. However, an entrepreneurial growth mindset does not have a significant direct impact on entrepreneurial performance. On the other hand, technopreneur competence has a positive and significant effect on entrepreneurial performance, this shows that the level of technopreneur competence plays a role in improving entrepreneurial performance. These results also reveal that the positive impact of an entrepreneurial growth mindset on entrepreneurial performance occurs through the mediator of technopreneurial competence, indicating the important role of technopreneurial competence in linking these two factors.